Impact of Cover Crop Management on Level of Weed Suppression: A Meta‐Analysis. Issue 3 (1st May 2019) - Osipitan, O. Adewale; Dille, J. Anita; Assefa, Yared; Radicetti, Emanuele; Ayeni, Albert; Knezevic, Stevan Z.
Abstract : We conducted a previous systematic and meta‐analysis review that showed differences in results from studies that evaluated the effectiveness of cover crops for weed suppression in cropping systems; these differences were largely due to management approaches used in growing the cover crop and main crop. The current meta‐analysis provides a quantitative review on how cover crop and main crop management practices influence the impact of cover crops on weed suppression. The meta‐analysis used observations from 53 studies published from 1990 to 2018. Cover crop biomass was inversely related to the amount of weed biomass ( r 2 = 0.67) and weed density ( r 2 = 0.64). In general, the meta‐analysis shows that cover crops provided a range of weed suppression depending on management decisions such as choice of cover crop species, cover crop sowing season (fall or spring), sowing dates within seasons, seeding rate, termination date, delay in main crop planting date after cover crop termination, tillage system under which the cover crop was produced, and integrating the cover crop with other weed control inputs. For example, grass cover crop species provided greater weed suppression than broadleaf species. Fall‐sown cover crops provided greater weed suppression (weighted mean of response ratio [ R* ] = 0.19) than spring‐sown cover crops ( R* = 0.48) by the summer. Weed suppression increased by increasing seeding rate of cover crops from 1× ( R* = 0.50) to 2× ( R* = 0.27) or 3× ( R* = 0.10). In addition, cover crops provided greater weed suppression in reduced tillage systems ( R* = 0.19) than no tillage ( R* = 0.29). The differential weed suppression provided by these management approaches suggests that a cover crop management approach should be rightly selected for weed suppression benefits.